Impregnabilnost in izpirljivost bakrovih zaščitnih pripravkov v odvisnosti od anatomske smeri lesa - Humar, Miha (Zbornik gozdarstva in lesarstva, 2007)
Due to the limited use of classical copper/chromium based preservatives, the industry seeks for alternatives for preservation of wood in ground applications. For such purposes, fungicides fixed in wood are utilised. For estimation of fixation, standard method that prescribes small specimens with higher portion of axial surfaces than in practice is utilised. The purpose of this article is to determine copper leaching from different anatomical planes.Orientated Norway spruce wood blocks were impregnated with aqueous solution of copper(II) sulphate and commercial preservative Silvanolin. The results showed comparable leaching from radial and tangential surfaces. However, more prominent leaching of copper(II) sulphate at higher concentrations and less extensive leaching of Silvanolin from axial surfaces was established.
Keywords: baker; etanolamin; impregnacija; lastnosti; zaščita lesa